Contribution of molecular diagnosis to bee venom allergic patients with systemic reactions during the build-up phase of bee venom immunotherapy - Lourenço, Tatiana (2019)
Introduction: Bee venom (BV) allergy is one of the most common causes of severe anaphylaxis. Venom immunotherapy (VIT) is considered the most effective treatment, but systemic reactions may occur. This study aimed to characterize the sensitization profile by molecular components of patients with BV anaphylaxis under VIT and to evaluate whether systemic reactions during the build-up phase of VIT protocol are related to different sensitization patterns. Methods: A retrospective study of 30 patients under VIT for 1 year. The group of patients who reacted during the build-up phase (group A) was compared with the group with no reactions (group B). Specific IgE (sIgE) and IgG4 (sIgG4) for BV and recombinants (rApi m1, rApi m2, rApi m3, rApi m5, and rApi m10) were evaluated before and 1 year after VIT. Statistical analysis was performed using GraphPad Prism v5.01. Results: Men accounted for 80% of the sample, and mean age was 47 years (14-74 years). Group A consisted of 10 patients, and group B of 20 patients. Before VIT, sIgE to rApi m1 was detected in 86.7% of patients, rApi m2 in 46.7%, rApi m3 in 16.7%, rApi m5 in 43.3%, and rApi m10 in 70%. Positive results to at least 1 BV allergen were detected in 100%; 73% of patients were sensitized to >1 allergen, and 13.3% to all allergens. The profile of the two groups did not differ significantly before VIT, but group B showed a significant decrease in whole BV extract (p=0.045), rApi m 3 (p=0.017), and rApi m 10 (p=0.021) 1 year after VIT. Regarding sIgG4, there was a significant increase in rApi m1, which was not observed in other allergens, such as rApi m3 and rApi m10. Conclusion: The analysis of a panel of BV recombinants can improve diagnostic sensitivity, when compared to rApi m1 alone. There was no association between systemic reactions during the build-up phase of VIT and molecular sensitization profile. Nevertheless, it is important to study a greater number of patients.